A REVIEW ARTICLE ON MECHANICAL PROPERTIES OF POROUS ASPHALT MIXTURE - KHALID, SHERZAD WAISY; AL-HADAD, BOTAN M. AHMAD (Journal of Duhok University, 2023)
Millions of kilometers of roads are constructed using asphalt mixtures, therefore; the environmental, safety, and economic factors are influenced by the materials and the methods used to prepare and implement such projects. The recent trend has focused on porous asphalt to search for alternative methods to the traditional method since the design and maintenance of asphalt mixtures are influential from an economic viewpoint. Moreover, the presence of water and a drainage system in the pavement is one of the elements that influences the composition of the pavement mixture and this has been evaluated through techniques adopted to design porous asphalt mixtures. This study reviews aspects of the materials, methods, and characteristics of porous pavement research articles to pinpoint the critical factors for understanding porous asphalt and its properties. This will make it possible to create techniques to optimize the performance of the mixture. This review article will conclude with ideas for new design strategies that use different materials and modifiers, as well as new methodologies for using porous asphalt in different classes of road pavements for better characteristics.